Study of the Catecholase Activity of new catalysts Based on Copper (II) and Heterocyclic Ligands - Rafika El Ati; Haytham Bouammali; Mohamed El Kodadi; El Bekkay Yousfi; Rachid Touzani; Belkheir Hammouti (Universitas Pendidikan Indonesia, 2022)
In this work, we are interested in finding new catalysts for catecholase, whose principle is based on the oxidation reaction of catechol to o-quinone. We approached the synthesis of the threes tripod ligands based on pyrazole in a condensation reaction and its characterization by IR, 13C NMR, 1H NMR spectroscopy, then we evaluated the catalytic properties of certain complexes formed in situ to catalyze the oxidation reaction of catechols to o-quinones. The aim is to find the right models to reproduce the catalytic activity of the enzyme (catecholase), we used complexes formed in situ by pyrazole derivatives with Copper salts. Among these complexes, the complex L4/Cu(CH3COO)2 showed good catalytic activity of the combination (1ligand/2metal) in MeOH for this reaction, with a speed Vmax equal to 69.38 μmol.L-1.min-1 and a low value of Km equal to 0.019 mol.L-1. We have demonstrated that the nature of concentration, ligand, solvent, and copper salts, influenced strongly the catecholase activity.